An observational study of distractions in the operating theatre. (17th August 2020) - van Harten, A.; Gooszen, H. G.; Koksma, J. J.; Niessen, T. J. H.; Abma, T. A.
Summary: Several studies have reported on the negative impact of interruptions and distractions on anaesthetic, surgical and team performance in the operating theatre. This study aimed to gain a deeper understanding of these events and why they remain part of everyday clinical practice. We used a mixed methods observational study design. We scored each distractor and interruption according to an established scheme during induction of anaesthesia and the surgical procedure for 58 general surgical cases requiring general anaesthesia. We made field notes of observations, small conversations and meetings. We observed 64 members of staff for 148 hours and recorded 4594 events, giving a mean (SD) event rate of 32.8 (16.3) h ‐1 . The most frequent events observed during induction of anaesthesia were door movements, which accounted for 869 (63%) events, giving a mean (SD) event rate of 28.1 (14.5) h ‐1 . These, however, had little impact. The most common events observed during surgery were case‐irrelevant verbal communication and smartphone usage, which accounted for 1020 (32%) events, giving a mean (SD) event rate of 9.0 (4.2) h ‐1 . These occurred mostly in periods of low work‐load in a sub‐team. Participants ranged from experiencing these events as severe disruption through to a welcome distraction that served to keep healthcare professionals active during low work‐load, as well as reinforcing the social connections between colleagues. Mostly, team members showed no awareness of the need for silence among other sub‐teams and did not vocalise the need for silence to others. Case‐irrelevant verbal communication and smartphone usage may serve a physical and psychological need. The extent to which healthcare professionals may feel disrupted depends on the situation and context. When a team member was disrupted, a resilient team response often lacked. Reducing disruptive social activity might be a powerful strategy to develop a habit of cross‐monitoring and mutual help across surgical and anaesthetic sub‐teams. Further research is needed on how to bridge cultural borders and develop resilient interprofessional behaviours.